То increase sowing quality of iattuce seeds ways of decreassing him the matrix differences - Н. В. Лещук (Plant Varieties Studying and Protection)
Revealed main point of formation the matrix differences of lettuce seeds characteristics (Lactuca sativa L.), its correlation with other categories of heterogeneity. It’s been shown the ways of decreasing of the matrix differences of lettuce seeds characteristics with the aim to increase sowing quality of seeds.